Penempatan Plang (Signage) Desa pada Decision Point Pengunjung Desa Kambingan - Saputra, Akhmad Andi; Ikhtisholiyah, Ikhtisholiyah; Hasti Suprihatin; Adi Mulya Kusuma (Jurnal Pengabdian Pada Masyarakat METHABDI, 2025)
The village has potential natural resources in agriculture and aquaculture ponds. Potential agriculture and ponds use a rainfed system to irrigate rice fields and ponds. In addition, Kambingan Village already has a permanent irrigation network. Cerme people certainly understand the access to Kambingan Village, but people from outside Cerme Subdistrict certainly need signage to Kambingan Village so they don't miss it when visiting the village. The type of road pavement entering the village is divided into 2 (two) types, namely paving pavement and asphalt pavement. The condition of the asphalt pavement is good, while the condition of the paving pavement is bumpy. The activity method in community service in Kambingan Village is the science and technology simulation method, where students redesign signage using design applications to create design concepts and engineering equipment for the fabrication and installation of signage. The stages carried out include identifying problems in the field, coordinating with the Village Chief, redesigning the signage board, fabricating the signage board, removing the old signage board, and installing new signage at a point determined by the Village Chief. The expected result is that the community gets information on directions to enter Kambingan Village through the installation of a new signage board and adds color or karaktek to the road shoulder from Cerme District to Benjeng District.